Al-IslÄm wa al-ThaqÄfah al-MahlÄ«yah: DirÄsah fÄ« Mujtamaâ€™ â€œEmbauâ€ fÄ« Kapuas Hulu KÄlimantÄn al-GharbÄ«yah - Hermansyah, Hermansyah (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2008)
The research for this piece was carried out in Embau - one of the sub districts of the region of Kapuas Hulu. Socio - demo graphically, this region is inhabited by n community of Muslims that that continues to grow in numbers. Further to the Muslims, the area is inhabited by considerable numbers of non-Muslim Dayaks and other migrants to the area. What is interesting to note is the process of Islamization of the Dayak community, which has occurred naturally as a result of its intersection with the Muslim community. It was the Malays, who appeared in the area hundreds of years ago, who brought Islam to the area. The introduction of Islam to the area has brought with it a number of changes to the Dayak community in West Kalimantan. Not only did many Dayaks adopt Islam as their religion, they further adopted the culture typical of other Muslims.DOI:Â 10.15408/sdi.v15i1.539